Callyspongiamides A and B, sterol O-acyltransferase inhibitors, from the Indonesian marine sponge Callyspongia sp. Issue 10 (1st June 2018) - Kapojos, Magie M.; Abdjul, Delfly B.; Yamazaki, Hiroyuki; Ohshiro, Taichi; Rotinsulu, Henki; Wewengkang, Defny S.; Sumilat, Deiske A.; Tomoda, Hiroshi; Namikoshi, Michio; Uchida, Ryuji
Graphical abstract: Abstract: Callyspongiamides A (1 ) and B (2 ), two new sterol O -acyltransferase (SOAT) inhibitors, were isolated from the Indonesian marine sponge Callyspongia sp. together with a known congener, dysamide A (3 ). The structures of 1 and 2 were elucidated to be polychlorine-containing modified dipeptides based on their spectroscopic data. Compounds 1 –3 inhibited both of the SOAT isozymes, SOAT1 and SOAT2, in cell-based and enzyme-based assays.